Transgenic Centipedegrass (Eremochloa ophiuroides [Munro] Hack.) Overexpressing S-Adenosylmethionine Decarboxylase (SAMDC) Gene for Improved Cold Tolerance Through Involvement of H2O2 and NO Signaling - Luo, Jianhao; Liu, Mingxi; Zhang, Chendong; Zhang, Peipei; Chen, Jingjing; Guo, Zhenfei; Lu, Shaoyun (Frontiers in Plant Science, 2017)
Centipedegrass (Eremochloa ophiuroides [Munro] Hack.) is an important warm-season turfgrass species. Transgenic centipedgrass plants overexpressing S-adenosylmethionine decarboxylase from bermudagrass (CdSAMDC1) that was induced in response to cold were generated in this study. Higher levels of CdSAMDC1 transcript and sperimidine (Spd) and spermin (Spm) concentrations and enhanced freezing and chilling tolerance were observed in transgenic plants as compared with the wild type (WT). Transgenic plants had higher levels of polyamine oxidase (PAO) activity and H2O2 than WT, which were blocked by pretreatment with methylglyoxal bis (guanylhydrazone) or MGBG, inhibitor of SAMDC, indicating that the increased PAO and H2O2 were a result of expression of CdSAMDC1. In addition, transgenic plants had higher levels of nitrate reductase (NR) activity and nitric oxide (NO) concentration. The increased NR activity were blocked by pretreatment with MGBG and ascorbic acid (AsA), scavenger of H2O2, while the increased NO level was blocked by MGBG, AsA, and inhibitors of NR, indicating that the enhanced NR-derived NO was dependent upon H2O2, as a result of expression CdSAMDC1. Elevated superoxide dismutase (SOD) and catalase (CAT) activities were observed in transgenic plants than in WT, which were blocked by pretreatment with MGBG, AsA, inhibitors of NR and scavenger of NO, indicating that the increased activities of SOD and CAT depends on expression of CdSAMDC1, H2O2, and NR-derived NO. Our results suggest that the elevated cold tolerance was associated with PAO catalyzed production of H2O2, which in turn led to NR-derived NO production and induced antioxidant enzyme activities in transgenic plants.